Positional Therapy for Obstructive Sleep Apnea: Therapeutic Modalities and Clinical Effects - Ki-Il Lee; Ji Ho Choi (Sleep Medicine Research, 2023)
Obstructive sleep apnea (OSA) is characterized by recurrent occurrences of partial or complete collapse of the upper airway during sleep, leading to shallow breathing or breathing pauses. These repeated breathing disruptions can result in intermittent hypoxia, hypercapnia, hyperactivity of the sympathetic nervous system, and fragmented sleep patterns. Left untreated, OSA can have significant health implications, including various symptoms and serious consequences. Positional OSA is a subtype of OSA where during sleep, the severity of apnea events is significantly higher in the supine position. This condition can worsen respiratory parameters, such as apnea/hypopnea events, oxygen desaturation and arousals, and cardiovascular burdens. Positional therapy is a treatment approach used for patients with positional OSA. Typically, positional therapy involves encouraging the patient to avoid sleeping on their back, and instead sleep in a lateral position. Various modalities for positional therapy exist, including positional training using a tennis ball, alarm, or vest, and sleep positioning pillows. Novel electric-operated postural devices have also been developed. Positional therapy has shown promise in improving apneic events and lowest oxygen saturation in patients with position-dependent sleep apnea. In comparison to positive airway pressure treatment, positional therapy has been reported to demonstrate non-inferior effects, while achieving better compliance. Consequently, positional therapy can be a cost-effective and non-invasive therapeutic alternative for managing positional OSA.